Analysis Of Factors Influencing Non-Performing Loans - Yahya, Adibah; Hidayat, Taufik; Pratiwi, Niken Cahyaning Mega (Proceeding International Pelita Bangsa, 2023)
The bank is an intermediary between parties needing funds and those with excess funds. The bank's main activity is channelling funds in the form of credit to parties who need funds. Credit distribution has a credit risk that arises when creditors cannot fulfil obligations according to the agreed time. Credit risk can be calculated using the Non-Performing Loan (NPL) ratio. This study aims to determine the effect of CAR, BOPO, LDR, ROA and LAR on NPL at PT. Bank Mandiri in 2001-2019. This research is a quantitative descriptive study, using multiple linear regression analysis techniques. The research object of PT. Bank Mandiri with saturated sampling technique. The results showed that CAR. BOPO, LDR, and LAR have no effect on NPL. Meanwhile, ROA has a negative effect on NPL.